Presence of Coronary Artery Disease in Patients on Methadone in the South Bronx: A Retrospective Analysis and Literature Review - M MD, Rodríguez-Guerra; Sahithi MD, Urlapu, Kinnera; Udanie, Hewapathirana; Itare MD, Vikram; Ked, MD, Fortuzi; Christian, MD, Mendoza; MD, Niel; Timothy, MD, Vittorio (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Our comunity has faced a challenge with the addiction to opioid, long acting medication like Methadone could be helpful in the setting of withdrawal, rehab, detox or chronic pain management, but also represent risk of dependence. Besides most of the litereatyre expose the relation between opiod could be related to cardiac disease, there is also a report relating methadone witha posible positive impact in coronary artery disease. Method: Retrospective and descriptive review of records and literature review. Result: Total of 207 of patient (pts) on methadone had coronary artery disease (CAD), of which 128 pts were known to have CAD from before, of this group the most common group was Hispanic between 45-64 years old. Regarding the cardiovascular (CV) risks, the 89.06% (114 pts) were hypertensive, 61.7% (79 pts) were diabetic, 24.21% (31pts) had Kidney disease with CKD III or more. 7% (9 pts) were known to have prolonged QTc, while 4.68% (6 pts) were newly diagnosed with it (Table 1). When we studied ejection fraction (EF), in the known CAD patients, we observed that the 20 % (26 pts) had EF < 40%, while the 10.16 % (13 pts) had intermediate EF (40-55%). Over the study period 97 pts had follow up echocardiography of with the 17.52% (17 pts) had improved EF, 64.94% (63pts) no change, while 17.52% (17 pts) had decreased EF. Regarding the cardiac events in this group, 13 patients had myocardial infarctions, of which six patients had ejection fraction below 40% and one patient had prolonged QTc (Table 2). Only 9.38% of the patients (12) had a follow up cardiac catheterization, of which 83% (10 pts) showed a progression of CAD. In the other hand, a total 38.16% (79 pts) had newly diagnosed with CAD, of which 62% (49 pts) were hypertensive, 37.97% (30 pts) had diabetes and 117.72% (14 pts) had CKD III or more. A total of 12.66% (10 pts) were known to have prolonged QTc while 6.33% (5 pts) were newly diagnosed with it. The 13.9% (11 pts) were found to have an improvement in ejection fraction while the 11.4% (9 pts) got worse. Two of these patients had myocardial infarction. (Table 3). Follow up echocardiograms showed that the ejection fraction did not get worse in 90 out of 116 patients. Overall only 1.93% (4 pts) had cardiac arrest of which 3 pts had prior history of CAD and none of them had prolonged QTc. Conclusion: This study has exposed the possibility of the positive effect of methadone in the cardiac pump function. There appears to be a progression of CAD in our patients who underwent to cardiac catheterization as a follow up, but due to the size of the sample of patient we cannot establish this relation as the definitive risk for the progression of the disease. Based on the literature review and our results, there is no doubt in the possible potential positive effect that long term use of opioids could have or maybe the negative cardiovascular effect, from the cardiac point of view. The incidence of fatal events did not represent a higher risk (Arrhythmias, myocardial infarction, or cardiac arrest) than the potential benefit (Improvement of heart function or mitigation of CAD).